Hubungan antara Pengurusan Masa dengan Tekanan Kerja dalam kalangan Guru Sekolah Menengah di Melaka - Saiful Hizan, Nor Safwan; Rodzalan, Shazaitul Azreen (Research in Management of Technology and Business, 2020)
Efficient time management and work stress play an important role for the teaching profession in secondary schools as it can help teachers to achieve success while doing work. The problem statement of this study is the workload and student misbehaviour that lead to work stress among teachers and thus affect time management. The main objective of this study was to study the level of time management and work stress among teachers. The study respondents consisted of secondary school teachers in Malacca. In addition, to identify the significant relationship between time management and teacher work stress as well as time management factors that influence the level of teacher work stress. The quantitative study was conducted using questionnaire instrument. The data obtained has been analysed using Statistical Package for Social Science (SPSS) software version 22.0. The results show that the level of work stress of teachers is moderate. Other than that, the results show that the mean for the highest time management factor is the planning factor. The results only revealed that there was a significant between two factors of time management which are mechanics of time management and preference for organization have shown a significant relationship to teacher work stress. Time management also contributes significantly to the level of time management with significant work stress. The results of this study will benefit the Ministry of Education Malaysia, teachers, and school management.